2014
DOI: 10.1111/jocn.12626
|View full text |Cite
|
Sign up to set email alerts
|

Effect of virtual reality distraction on pain among patients with hand injury undergoing dressing change

Abstract: Virtual reality distraction can effectively relieve pain without side effects and is not reliant on a doctor's prescription. This tool is convenient for nurses to use, especially when analgesics are unavailable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
71
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 15 publications
(17 reference statements)
2
71
1
1
Order By: Relevance
“…Due to recent technical advances, VR distraction has become increasingly available and is used in acute pain management ( Garrett et al, 2014 ; Hoffman et al, 2006 ; Rutter, Dahlquist, & Weiss, 2009 ). Using VR has been shown to reduce pain during burn treatment ( Guo, Deng, & Yang, 2015 ; Kipping, Rodger, Miller, & Kimble, 2012 ; Schmitt et al, 2011 ). More recently, in the context of dental care, one study demonstrated that distracting children with 3D video glasses during administration of local analgesia resulted in a reduction of anxiety ( Nuvvula, Alahari, Kamatham, & Challa, 2015 ).…”
mentioning
confidence: 99%
“…Due to recent technical advances, VR distraction has become increasingly available and is used in acute pain management ( Garrett et al, 2014 ; Hoffman et al, 2006 ; Rutter, Dahlquist, & Weiss, 2009 ). Using VR has been shown to reduce pain during burn treatment ( Guo, Deng, & Yang, 2015 ; Kipping, Rodger, Miller, & Kimble, 2012 ; Schmitt et al, 2011 ). More recently, in the context of dental care, one study demonstrated that distracting children with 3D video glasses during administration of local analgesia resulted in a reduction of anxiety ( Nuvvula, Alahari, Kamatham, & Challa, 2015 ).…”
mentioning
confidence: 99%
“…This mechanism has anecdotally proposed by other VR rehabilitation studies (Perry et al, 2014). Alternatively, VR systems have been used to distract attention from pain (Keefe et al, 2012;Guo et al, 2014;Walker et al, 2014;Wiederhold et al, 2014) and decrease negative emotions about pain (Herrero et al, 2014;Triberti et al, 2014;Garcia-Palacios et al, 2015). The VR environment itself might distract attention and thus decrease pain (Wiederhold et al, 2014).…”
Section: Discussionmentioning
confidence: 94%
“…One study found that an amputee patient who perceived a vivid subjective experience of moving their phantom limb reportedly showed the bimanualcoupling effect during the BCT, although another patient without this experience did not show the coupling effect (Franz and Ramachandran, 1988). Alternatively, VR systems have been used to distract attention from pain (Keefe et al, 2012;Guo et al, 2014;Walker et al, 2014;Wiederhold et al, 2014) and decrease negative emotions about pain (Herrero et al, 2014;Triberti et al, 2014;Garcia-Palacios et al, 2015). A high OI associated with BCT performance would indicate vivid movement representations of the affected hand (drawing circles), independent of real movements.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies focusing on affective interventions showed that VR can be employed as a distraction mechanism, both for chronic pain [24], but also instant pain [4]. For instance, Trost and Parsons [24] devised a VR paradigm with Kinect, exposing sufferers to graded therapy regimes for chronic pain with promising results regarding its applicability, affordability and wide accessibility.…”
Section: Related Workmentioning
confidence: 99%
“…For instance, Trost and Parsons [24] devised a VR paradigm with Kinect, exposing sufferers to graded therapy regimes for chronic pain with promising results regarding its applicability, affordability and wide accessibility. Guo, Deng and Yang [4]have utilised VR interventions for instant pain distraction of patients with upper limb injuries undergoing dressing changes with empirical results on the effectiveness of the intervention for both patients and professionals. Another example of how VR can be used for affective interventions is presented by Gromala et al [3].…”
Section: Related Workmentioning
confidence: 99%